2011
DOI: 10.1111/j.1582-4934.2011.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

NK receptors, Substance P, Ano1 expression and ultrastructural features of the muscle coat in Cav-1−/− mouse ileum

Abstract: Caveolin (Cav)-1 is an integral membrane protein of caveolae playing a crucial role in various signal transduction pathways. Caveolae represent the sites for calcium entry and storage especially in smooth muscle cells (SMC) and interstitial cells of Cajal (ICC). Cav-1−/− mice lack caveolae and show abnormalities in pacing and contractile activity of the small intestine. Presently, we investigated, by transmission electron microscopy (TEM) and immunohistochemistry, whether the absence of Cav-1 in Cav-1−/− mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Although significant, the changes were not dramatic, with small changes observed in Hsp70 and Hsp27 and even less in Gp96. While it is generally accepted that Cav-1 is essential for the formation of caveolae, a recent study has shown by electron microscopy that intestinal cells may still form large size caveolae in the absence of Cav-1 (Cipriani et al 2011), indicating that these cells have Fig. 2 Representative images of the levels of Hsp70, Hsp27, and Gp96 as revealed by IHC.…”
Section: Discussionmentioning
confidence: 97%
“…Although significant, the changes were not dramatic, with small changes observed in Hsp70 and Hsp27 and even less in Gp96. While it is generally accepted that Cav-1 is essential for the formation of caveolae, a recent study has shown by electron microscopy that intestinal cells may still form large size caveolae in the absence of Cav-1 (Cipriani et al 2011), indicating that these cells have Fig. 2 Representative images of the levels of Hsp70, Hsp27, and Gp96 as revealed by IHC.…”
Section: Discussionmentioning
confidence: 97%
“…103,104 More recently, it has been shown that ICC are anoctamin-1 (ANO1) negative in mice that lack caveolae (caveolin-1 knockout mice). 105 ANO1 is a calcium activated chloride channel that is fundamental to the generation of slow waves, 106,107 again suggesting an important role for caveolae in pacemaker activity. An abundance of mitochondria has been observed in ICC and these organelles are in close apposition to the ER and the plasma membrane (PM).…”
Section: Interstitial Cells Of Cajal As Pacemakers Of the Gastrointesmentioning
confidence: 99%
“…Intracellular calcium oscillations periodically activate plasmalemmal channels, such as Ca 21 -activated Cl 2 channels (Takaki et al, 2010). Anoctamin 1 (Ano1, TMEM16A, DOG1) is a major component of the plasmalemmal Ca 21 -activated Cl 2 channels (CaCCs) (Ferrera et al, 2010;Cipriani et al, 2011;Kunzelmann et al, 2011;Shimizu et al, 2013;Simon et al, 2013). In this regard, the evidence of a sublayer of DOG1 positive ICC-MY is suggestive for a subpopulation of ICC-MY being qualified for pacemaking at this early developmental stage.…”
Section: Discussionmentioning
confidence: 99%